The Function of Bank Negara Malaysia in Combating Money Laundering on International Basis - Shahrudin, Eskandar Shah (2013)
Money laundering issues started to receive much attention after the tragic event of 11th September 2011. Developing countries such as Malaysia was identified by Pentagon as one of the countries where illegal funds travelled into the country in order to become legitimate. This had sent a strong signal to the Malaysian government that the country’s financial system is vulnerable to such money laundering activities. As a result Bank Negara Malaysia as the central bank of the country, had been assigned by the government to ensure the financial system is not used as a medium to launder money. This had led to the establishment of Bank Negara Malaysia Financial Intelligence Unit (BNM FIU) in 2002 which is responsible in receiving, analysing and disseminating financial intelligence information to the relevant law enforcement agencies in order to fight money laundering. The severity of money laundering is very much attributed to the factors such as globalisation, advancement of technology and communication, as well as cross-border financial transaction activities. As money laundering could be spread across countries, involving numerous jurisdictions, BNM FIU has an important role to ensure the severity of money laundering affecting the domestic financial players could be mitigated. In this context, international cooperation with other related international bodies such as the Financial Intelligence Units of other countries is deemed important for the benefit of exchanging and sharing of financial intelligence information. As international cooperation involves different jurisdictions and regulations, BNM FIU may face obstacle that may result in slower process of receiving and analysing the said information. Although such obstacle is unavoidable, the question is to what extent does BNM FIU play a major role in international cooperation? This could be seen in the actions taken by BNM FIU which include voluntarily disclosure of financial intelligence information, the signing of Memorandum of Understandings (MOUs), training and learning programmes to foreign counterparts as well as disclosure to foreign FIUs. In this context, comparison is also made between BNM FIU with other South East Asia region’s FIU in order to gauge their level of international cooperation. Although BNM FIU is regarded as one of the leading FIUs in the South East Asia region in terms of international cooperation, the declining trend involving voluntarily disclosure of financial intelligence information, signing of MOUs, as well as training and learning programmes to foreign counterparts within the period of year 2008 to 2011 is rather alarming. The interview with the Deputy Director of BNM FIU would highlight the reasons of such declining trend and why international cooperation is still an important criteria for BNM FIU in combatting money laundering on international basis.